Physicochemical, Antioxidant and Sensory Evaluation of Dark Chocolate Fortified with Sacha Inchi Powder Roasted at Different Condition - Azhar, Fathiah Nabila Azhar; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2025)
The increasing demand for functional foods had led to a raised interest in fortifying chocolate with nutrient-rich ingredients. This research investigates the enhancement of dark chocolate via the incorporation of sacha inchi powder, a natural source of omega-3 polyunsaturated fatty acids (PUFAs), antioxidants and phenolic compounds. The impact of sacha inchi powder, roasted at two temperatures (T80 and T160) for 15 minutes, was assessed on the physicochemical parameters, antioxidant activity, total phenolic content (TPC) and sensory characteristics of fortified dark chocolate. Sacha inchi powder obtained from Pantai, Negeri Sembilan was added at levels of 3, 5 and 7% (w/w) into melted dark chocolate. The hardness of fortified dark chocolate samples obtained are lower (0.82kg±0.02–1.07kg±0.02) compared to control sample (1.10kg±0.07) with fortification significantly (p<0.05) reduced the hardness of chocolate, especially at higher fortification levels (5 and 7%). Moisture content of fortified chocolate (0.38%±0.02-0.75%±0.04) increased significantly (p<0.05) at 5% and 7% due to hygroscopic nature of sacha inchi powder, while the control sample recorded 0.69%±0.11. The colour parameters (L*, a*, b*) were uniform (ranged from 35.29±0.13 to 37.18±0.54, -1.33±0.19 to -4.87±0.06 and -4.87±0.06 to -4.30±0.09, respectively) among the samples, exhibiting no significant differences (p>0.05). Antioxidant activity (72.02%±0.24–89.13%±0.53) and TPC (21.08±0.03–40.82mg GAE/g±0.36) enhanced with elevated amounts of sacha inchi powder, particularly at T160, attributable to the Maillard reaction products and preservation of tocopherols. Sensory evaluation indicated that dark chocolate fortified with 5% of T160-roasted sacha inchi powder (DC5) had the greatest ratings for taste, colour, aroma, texture and overall acceptability among the fortified samples, despite the control sample being favoured overall. This study illustrates the efficacy of sacha inchi powder as a functional component in dark chocolate, improving its nutritional profile while preserving sensory characteristics. Sacha inchi-fortified chocolate can be promoted as a heart-healthy, antioxidant-rich snack that supports well-being.